THE RELATIONSHIP OF TEACHERS' INTERPERSONAL COMMUNICATION AND VISUAL LEARNING STYLES ON THE INDEPENDENCE OF ENGLISH LEARNING STUDENTS OF SHAFIYYATUL AMALIYYAH MEDAN - Mehri Hubbi Apmarja; Hasanuddin; Suaidah Lubis (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
English learning independence is currently problematic in carrying out the learning process. English learning independence is certainly influenced by many factors. This study aims to analyze and determine the relationship between teacher interpersonal communication and visual learning styles on students' English learning independence. This study is included in quantitative research with an associative causal nature. The sample of this study was 168 students spread across Saffiyatul Amaliyah students. The research data were collected using a research scale that was declared valid and reliable. The data analysis technique used multiple linear regression analysis. The results of the study showed that (1)There is a relationship between teacher interpersonal communication and students' English learning independence.Based on the results of the study, it was found that the regression coefficient value of the Interpersonal Communication variable (X1) was 0.329, which is positive. This means that Teacher Interpersonal Communication (X1) has a positive effect on English Learning Independence (Y). It is known that the t statistic or t count of Interpersonal Communication (X1) is 4.863> t table = 1.97 and the Sig. value is 0.000, which is <0.05 significance level, then Interpersonal Communication (X1) has a significant effect on English Learning Independence (Y). So it can be concluded that Teacher Interpersonal Communication (X1) has a positive and significant effect on English Learning Independence (Y).(2)There is an influence of visual learning style on students' independence in learning English.Based on the research results, it was found that the regression coefficient value of the Visual Learning Style variable (X2) was 0.106, which is positive. This means that when the Visual Learning Style (X2) increases by 1 unit, the English Learning Independence (Y) tends to increase by 0.106. It is known that the t statistic or t count of the Visual Learning Style (X2) is 1.997> t table = 1.97 and the Sig. value is 0.047, which is <0.05 significance level, then the Visual Learning Style (X2) has a significant effect on English Learning Independence (Y).(3)There is an influence of interpersonal communication between teachers and visual learning styles on students' English learning independence., Based on the results of the hypothesis test that has been carried out, it was found that the calculated F value is 13.965 and the Sig. value is 0.000. It is known that the calculated F value is 13.965 > F table 3.050 and the Sig. value is 0.000 < 0.05, then Interpersonal Communication (X1) and Visual Learning Style (X2) together or simultaneously have a significant effect on English Learning Independence (Y), and the coefficient of determination (R-Square) is 0.145. This value can be interpreted that the variables Interpersonal Communication (X1) and Visual Learning Style (X2) are able to influence English Learning Independence (Y) by 14.5%. it can be concluded that the visual learning style and teacher interpersonal communication together have an effect on English learning independence in students. The contribution of both in influencing learning independence is 14.5%. the remaining 100% - 14.5% = 85.5% is explained by other variables or factors.